Development of Problem-Based Learning Dart board Media for Herbal Botany Course - Marwah, Andi Sitti; Wally, Pramita (INSTITUT AGAMA ISLAM NEGERI AMBON, 2024)
Improvement in student learning outcomes depends on the lecturer's ability to use media in the learning process. The availability of adequate media can certainly make learning not only interesting but also effective. The Dart board learning media is one of the media that needs to be developed because it can be used in Herbal Botany learning. This research uses a Research and Development (R&D) approach. The purpose of this research approach is to analyze the ability and effectiveness of the learning media using the dart board. This type of research aims to produce a dart board learning media that is valid, effective, and practical. This research follows the 4-D model of development. The results show that the average pre-test score of students before using the dart board learning media was <56, but after using the dart board learning media, the average post-test score of students increased to >79. Thus, learning using the Dart board media in the Herbal Botany course can increase enthusiasm and improve student learning outcomes. Keywords: Learning Media, PBL, Dart board